Resistance to Six Aminoglycosidic Aminocyclitol Antibiotics Among Enterococci: Prevalence, Evolution, and Relationship to Synergism with Penicillin - Calderwood, Susan Adams (1977)
Two hundred and three recent clinical isolates of enterococci were tested for susceptibility to streptomycin, kanamycin, amikacin, gentamicin, sisomicin, and tobramycin. Depending upon the source of the isolate, 36 to 54% of the enterococci demonstrated high-level resistance (minimal inhibitory concentration, >2,000 μg/ml) to streptomycin, 16 to 49% to kanamycin, and 0 to 14% to amikacin. None of the strains was highly resistant to gentamicin, sisomicin, or tobramycin. A comparison with isolates of enterococci obtained in 1968 revealed that there has been a decrease in prevalence of high-level resistance among organisms isolated from wound cultures in 1976. However, no decrease in resistance to streptomycin or kanamycin was demonstrated among blood or urine isolates. Penicillin, combined with gentamicin, sisomicin, or tobramycin, was synergistic against all 10 strains of Streptococcus faecalis subjected to formal testing. For streptomycin and kanamycin, the presence or absence of synergism with penicillin correlated with the absence or presence of high-level aminoglycoside resistance. High-level resistance to amikacin was seen in only 1 of the 10 strains. Nonetheless, combinations of penicillin plus amikacin failed to produce synergistic killing against 6 of the 10 strains. Indeed, the combination was synergistic only against those four strains that were susceptible to high levels of kanamycin.